Evaluation of cellulosic wastes for the cultivation of Pleurotus eryngii (DC. ex Fr.) Quel - Akyuez, Mehmet; Yildiz, Abdunnasir (Academic Journals, 2008)
This study investigated the possible use of local cellulosic wastes for the cultivation of Pleurotus eryngii (DC. ex Fr.) Quel. var. ferulae Lanzi and Pleurotus eryngii (DC. ex Fr.) Quel. For the propagation of the main culture, 2.0% malt-extract agar was used whereas barley grains were used for the propagation of spawn. For the formation of basidiocarp, wheat straw (WS), soybean straw (SS) and bran of rice (RB) were used as culture media. Three types of compost were prepared: a mixture of WS-SS (1: 1), WS and SS. The three compost types were also supplemented with 5.0 and 10.0% of RB. The shortest mycelium growing period was determined as average 8 days on SS and the longest period was 17 days on WS + 10.0% RB. In addition, the shortest mycelium growing period for P. eryngii var. ferulae was determined as average 12 days on WS + 10.0% RB, while the longest period was 18 days on WS-SS (1: 1) + 5.0% RB. The shortest primordium formation period for P. eryngii was determined as 36 days on SS + 10.0% RB, while the longest period was 95 days on WS + 5.0% RB. In addition, for P. eryngii var. ferulae, there was no basidiocarp formation on any trial after mycelium growth on the compost even after 108 days of culture. The first harvest period for P. eryngii was determined as average 48 days on SS + 10.0% RB, and the total harvest period was 108 days on WS + 5.0% and WS + 10.0% RB. The highest biological efficiency ( BE) was 93% on WS-SS (1: 1) + 5.0% RB and the lowest BE was 7% on WS + 10.0% RB. The lowest average yield per 100 g of material (70% moisture) was 2.0 g on WS + 10.0% RB, while the highest yield was 28.0 g on WS-SS (1: 1) + 5.0% RB. In conclusion, various local agricultural wastes can be used for the cultivation of P. eryngii.
Keywords: cultivation; Pleurotus eryngii; Pleurotus eryngii var. ferulae; cellulosic wastes; yield